2022
DOI: 10.3168/jds.2021-20165
|View full text |Cite
|
Sign up to set email alerts
|

Proper motility enhances rumen fermentation and microbial protein synthesis with decreased saturation of dissolved gases in rumen simulation technique

Abstract: The physiological function of the reticulorumen plays an essential role in ruminant nutrition, and detailed knowledge of rumen motility can further advance understanding of ruminant nutrition and physiology. Rumen motility was simulated by setting different stirrer rotation speeds in a rumen simulation technique (RUSITEC) system. The aim of this study was to investigate the effects of rotation speeds on rumen fermentation, saturation factor of dissolved gases, hydrogen (H 2 ) and methane (CH 4 ) emissions, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
2
18
0
1
Order By: Relevance
“…Although this effect is counteracted by water flux from the bloodstream (through saliva or directly entering across rumen wall) L-Carnitine, a compound with osmoprotectant properties, may have allowed more susceptible bacteria to overcome osmotic stress ( Meadows and Wargo, 2015 ), whereas it is plausible that microbiota of the control lambs had to use some nutrients to synthesize L-Carnitine or other osmoprotectants to be adapted against changes in osmotic pressure, thus modifying ruminal fermentation parameters. Likewise, it has been reported that carnitine supplementation can modulate gut motility ( Meyer et al, 2020 ) and transit time, which is another factor that affects gut microbiota composition and fermentation ( Tottey et al, 2017 ; Adebayo Arowolo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this effect is counteracted by water flux from the bloodstream (through saliva or directly entering across rumen wall) L-Carnitine, a compound with osmoprotectant properties, may have allowed more susceptible bacteria to overcome osmotic stress ( Meadows and Wargo, 2015 ), whereas it is plausible that microbiota of the control lambs had to use some nutrients to synthesize L-Carnitine or other osmoprotectants to be adapted against changes in osmotic pressure, thus modifying ruminal fermentation parameters. Likewise, it has been reported that carnitine supplementation can modulate gut motility ( Meyer et al, 2020 ) and transit time, which is another factor that affects gut microbiota composition and fermentation ( Tottey et al, 2017 ; Adebayo Arowolo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used a dual-flow continuous culture fermentation system because continuous culture fermenters run continuously for longer periods than in the Daisy II , batch culture and the Ankon Gas Production System, furthermore, the continuous culture can mimic in vivo ruminal conditions and allows for natural stratification of feed particles, anaerobiosis, controlled temperature, and salivary buffering, similar to what occurs in the rumen (Alende et al 2018 ). A dual-flow continuous culture system (Adebayo Arowolo et al 2021 ) was used in this study. This system contains six fermentation units, each unit consisting of a fermentation apparatus, outflow device, liquid supply component, data detection module and controlling computer.…”
Section: Methodsmentioning
confidence: 99%
“…Each round experiment included two cow rumen contents (cow group), two goat rumen contents (goat group), and two mixed contents of cow and goat rumen (co-inoculum group). A modification was made based on the previously described method of diluting inoculum 12 , which takes the total biomass as a consideration. Two rounds of cow rumen inocula (DNA concentration: 28.93 ± 2.91 μg/mL; 23.65 ± 0.27 μg/mL) were diluted 1.18 and 1.28-fold respectively with McDougall buffer solution, while the goat rumen inocula (DNA concentration: 24.48 ± 0.15 μg/mL; 18.42 ± 0.69 μg/mL) were diluted 0.84 and 0.77-fold respectively.…”
Section: Methodsmentioning
confidence: 99%